O jornalismo como ferramenta política do discurso sobre a terra em Mato Grosso - Santos, Luana Souza (2020)
This work aims to reflect on, under the ideological point of view, the professional qualification and practice of journalists in the state of Mato Grosso. This relates to a growing national demand of agricultural productive sectors by specialized qualification on the news coverage related to the agrarian sector and to the hegemonic speech of policies associated with the country ́s land. These two subjects, Journalism and Agri- environmental Policy, present themselves in particular moments. The first one faces, paradoxically, a period of depreciation of the specific qualification and professional regulation, caused by major communication companies, while other companies outlets demand not just an academic degree in the area, but also additional specialization. The second one consolidates in Brazil, an inverse process from what we can observe even in more developed capitalist countries, with incentive of land concentration, monoculture production, and consequently the growth of conflicting relations with farmhand and the native population. The aim of the research is to analyze, in the critical view, if and how Journalism legitimizes the dialogue that strengths this logic and what are the interests and the relations of power that presents the necessity of specialization for the news coverage related to Agribusiness and Environmental topics beyond the reflections and contradictions of this relation. For that, it was carried out a bibliographic survey with a selection of documents and a study case in a region of conflict in the state of Mato Grosso. The results colaborate with the debate surrounding the important topics. These include Rural Sociology and the Environment, together with the Brazilian social dynamic considering the political context of labor and social rights withdrawal, where the influence of the so-called “rural caucus” in Brazilian’s National Congress has been highlighted, through bargains, which jeopardize the progress made in relation to the standards of inspection and environmental preservation areas, among others.